Building Awareness on the Importance of Body Fluids - Fasrini, Ulya Uti; Welan, Rahmani; Anggraini, Fika Tri (Asian Journal of Community Services, 2024)
Water makes up two-thirds of the composition of the human body. The body's need for water can eliminate thirst and prevent several health problems due to dehydration. Dehydration will cause a person to not focus on thinking, mood changes occur, increased body heat, and digestive disorders. The webinar theme raised is Hydration and Achievement, which aims to increase the knowledge capacity of webinar participants, who come from the general public and health workers, focusing on hydration, body fluid fundamentals, and health. The webinar method delivers material by two experts and oral presentations from three students. The results of the webinar pooling showed that the participants were interested in participating because they wanted to add knowledge.